Justin the Seer: Viewing Christian Truth in the Second Century - Abbott, Philip (Zeitschrift für antikes Christentum, 2025)
This article argues that a central component of Justin Martyr’s thought is his ocularcentric orientation. In his Apologies and Dialogue with Trypho , Justin draws on several ancient discourses of vision to produce a new worldview centered on Christ’s incarnation. For Justin, the incarnate Logos embodied all previous enlightenment and visually revealed the full manifestation of truth. Christ also performed miracles that visibly proved his divinity. Furthermore, he established the Christian tradition whose validity was still visibly evident in Justin’s day. For Justin, this observable evidence for Christian truth included the valiant lives and martyrdoms of Christians, powerful exorcisms performed in Christ’s name, the expansion of Christianity among all nations, and the fulfillment of prophetic scripture. According to Justin, all these phenomena visually proved the truth of Christianity, which was inherently an ocular movement.